No difference in implant survival between 28-mm M2a RingLoc metal-on-metal and metal-on-polyethylene total hip arthroplasty: results from the Finnish Arthroplasty Register - Palomäki, Antton; Hemmilä, Matias; Matilainen, Markus; Eskelinen, Antti; Haapakoski, Jaason; Puhto, Ari-Pekka; Kettunen, Jukka; Pamilo, Konsta; Manninen, Mikko; Vasara, Anna; Mäkelä, Keijo T (Acta orthopaedica, 2022)
Background and purpose: Long-term outcome of small head (28 mm) metal-on-metal (MoM) total hip arthroplasty (THA) is available mainly for Metasul devices (Sulzer Medica, Winterthur, Switzerland). Biomet MoM THA was frequently used in Finland. Therefore, we assessed long-term survivorship of the M2a 28-mm RingLoc MoM THA (Biomet, Warsaw, IN, USA) and compared it with the metal-on-polyethylene (MoP) RingLoc THA from the same manufacturer.Patients and methods: We conducted a register study based on THAs from the Finnish Arthroplasty Register performed between January 1, 2000 and December 31, 2007. 290 28-mm head M2a MoM THAs and 1,647 28-mm head MoP THAs (reference group) were included. The endpoint was revision for any reason, or revision for aseptic loosening, osteolysis, liner wear, or metallosis as one group. Kaplan–Meier survival estimates were calculated, and revision risks were assessed using a Cox multiple regression model, both with 95% confidence intervals (CI).Results: No difference was found in the 15-year Kaplan–Meier survivorship between the 28-mm head M2a RingLoc MoM THA and the reference group for any reason for revision (87.7% [82.9–92.1] and 83.3% [81.0–85.3], respectively). The adjusted hazard ratio (HR) for any reason for revision for the MoM THA group compared with the reference group was at least equal or better (0.70 [0.48–1.02]). Both groups presented similar survival for revision for aseptic loosening of the cup, osteolysis, liner wear, or metallosis, at 96.2% (92.7–98.0) and 95.4% (93.9–96.5), respectively.Interpretation: In the long-term survival there was no difference between the M2a 28-mm RingLoc MoM THA and 28-mm MoP THA. Further follow-up regimens for M2a 28-mm RingLoc THA patients may be unnecessary, but long-term metal ion and radiological data is needed before any formal suggestions.